2018
DOI: 10.3349/ymj.2018.59.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Placenta-Derived Mesenchymal Stem Cells in a Dementia Rat Model via Microglial Mediation: a Comparison between Stem Cell Transplant Methods

Abstract: PurposeLoss of cholinergic neurons in the hippocampus is a hallmark of many dementias. Administration of stem cells as a therapeutic intervention for patients is under active investigation, but the optimal stem cell type and transplantation modality has not yet been established. In this study, we studied the therapeutic effects of human placenta-derived mesenchymal stem cells (pMSCs) in dementia rat model using either intracerebroventricular (ICV) or intravenous (IV) injections and analyzed their mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The performance of all rats in all groups gradually improved across 5 days of MWM training, suggesting that rats with cholinergic dysfunction have a similar level of learning capacity and escape latency compared with wild-type rats (Fig. 6) [34, 35]. In the probe test, when compared with the control and FUS groups, the SAP group displayed a diminished MWM performance 72 h after final training, as measured by the number of crossing over the platform area and time spent, which complements the findings of previous studies [33–36, 44].…”
Section: Discussionmentioning
confidence: 99%
“…The performance of all rats in all groups gradually improved across 5 days of MWM training, suggesting that rats with cholinergic dysfunction have a similar level of learning capacity and escape latency compared with wild-type rats (Fig. 6) [34, 35]. In the probe test, when compared with the control and FUS groups, the SAP group displayed a diminished MWM performance 72 h after final training, as measured by the number of crossing over the platform area and time spent, which complements the findings of previous studies [33–36, 44].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of MSCs were mainly attributed to the activity of MSC-derived products (conditioned medium (MSC-CM) and exosomes (MSC-Exos)): nanosized extracellular vesicles that, in a paracrine and endocrine manner, delivered proteins, lipids, DNA fragments, and mRNA to the immune, endothelial, and alveolar epithelial cells modulating their function [20]. Several lines of evidence suggested that MSCs derived from placental tissues (PL-MSCs) had superior biological properties compared to MSCs derived from adult tissues [21][22][23][24]. In line with these findings, we recently developed the "Exosome-derived Multiple Allogeneic Protein Paracrine Signaling (Exo-d-MAPPS)," a PL-MSC-derived product whose activity is based on exosomes, growth factors, and immunomodulatory cytokines capable of attenuating inflammation and promoting the regeneration of injured tissues [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clonal subpopulations of PL-MSCs have been attributed with the potential to differentiate into tissues from all three germ layers. Accordingly, due to their capacity for neuronal differentiation, PL-MSCs have been proposed as one of the main candidates for stem cell therapy of multiple sclerosis, nerve injuries, and sensorineural hearing loss (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%